Elementary school EFL learners' vocabulary learning: The effects of post-reading activities - KURT TİFTİK, GÖKÇE (CANADIAN MODERN LANGUAGE REV, 2006)
As language learning involves the acquisition of thousands of words, teachers and learners alike would like to know how vocabulary learning can be fostered, especially in EFL settings where learners frequently acquire impoverished lexicons, despite years of formal study. Research indicates that reading is important but not sufficient for second-language vocabulary learning, and that it should be supplemented by post-reading activities to enhance students' vocabulary knowledge. The present study investigates the effects of two types of post-reading activities: discrete written tasks on their own and a combination of written tasks along with interactive tasks on the vocabulary acquisition of young learners in an EFL setting. A total of 62 Grade 6 students in two classes in a public school in Turkey participated in the study. Data were collected by the Cambridge English Test (CYLET) and Vocabulary Knowledge Scale (VKS). Results showed that the experimental group students outperformed the control group students in acquisition of both selected and unselected vocabulary items. The use of interactive tasks as post-reading activities proved to be an effective way of enhancing the L2 vocabulary knowledge of young learners. (c) 2006 The Canadian Modern Language Review.
Keywords: ACQUISITION; LANGUAGE; COMPREHENSION; INSTRUCTION; LITERACY; WORDS